骨代谢标志物ICTP、BAP对肺癌骨转移的诊断意义 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Bone metabolic markers are biomarkers derived from bone matrix or osteocyte reflecting bone metabolic situation. The aim of this study is to explore the diagnostic value of bone markers, cross-linked telopeptide of type Ⅰ collage (ICTP) and bone-specific alkaline phosphatase (BAP) in lung cancer patients with bone metastases (B.M). METHODS: As a prospective control study, 110 cases were enrolled and divided into 3 groups. Totally 90 pre-treated, stage Ⅳ lung cancer cases were divided into two groups: 50 cases with bone metastases, 40 cases without bone metastases, as well as 20 healthy subjects were included as control. Serum ICTP was detected by enzyme-linked immunoassay (ELISA) and serum BAP was detected by electrochemiluminescence immunoassay. The relationships between factors of B.M and serum levels of ICTP, BAP were analyzed. RESULTS: The levels of serum ICTP and BAP in lung cancer patients with B.M were significantly higher than those in the healthy controls and those without B.M (P < 0.05). The level of serum BAP in patients with multiple B.M (lesions≥3) was significantly higher than that in patients with few B.M (lesions < 3) (P < 0.05). The level of serum BAP in patients with mixed pattern was significantly higher than that with lytic pattern. The sensibility of ICTP and BAP in the diagnosis of B.M in lung cancer patients was 18% and 40% respectively. The specificity of ICTP and BAP was 98.3% and 95% respectively. The accuracy rates of ICTP and BAP were 61.8% and 70.0% respectively. Joint detection of ICTP and BAP had improved sensibility and accuracy in the diagnosis of bone metastases in lung cancer patients (52% and 74.5% respectively). CONCLUSION: Serum bone biochemical markers ICTP and BAP have diagnostic values for B.M in lung cancer patients with lower costs, noninvasiveness and convenience.